Antecedents and consequences of perceived autonomy support in elite sport: A diary study linking coaches' off-job recovery and athletes' performance satisfaction. (September 2019) - Balk, Yannick A.; de Jonge, Jan; Geurts, Sabine A.E.; Oerlemans, Wido G.M.
Abstract: Objectives: To preventpoor health and well-being resulting from the high demands of coaching in elite sport, coaches need to recover during time away from work. This can benefit coaches' own work experiences as well as their interpersonal behaviour towards athletes. Therefore, the first aim of this study was to investigate within-person associations between elite coaches' off-job recovery (i.e., physical, cognitive, and emotional detachment from work), physical fatigue, positive affect, work engagement, and perceived autonomy support. The second aim was to investigate within-person associations between elite athletes' daily perceptions of autonomy support, athlete engagement, and performance satisfaction. Design: A one-week daily diary study was conducted. Method: Thirty-one elite coaches (30 males, 1 female) and 96 elite athletes (67 males, 29 females) completed online daily surveys across eight consecutive days. Results: Multilevel structural equation modelling showed that coaches' daily off-job physical detachment was negatively related to physical fatigue the next morning, whereas daily off-job emotional detachment was positively related to positive affect the next morning. Physical fatigue and positive affect were positively and negatively related to daily work engagement, respectively, which in turn was positively related to athletes' perceptions of autonomy support. For athletes, daily athlete engagement fully mediated the relation between daily perceived autonomy support and daily performance satisfaction. Conclusions: This study shows that off-job recovery, in terms of physical and emotional detachment from work, is not only important for elite coaches' health, well-being, and work engagement but also benefits elite athletes' daily sport experiences. Highlights: We investigated daily off-job recovery experiences among elite coaches. Detachment from work predicted elite coaches' fatigue and negative affect. Coaches' fatigue and negative affect before work was related to work engagement. Coaches' work engagement predicted autonomy-supportive behaviour towards athletes. Coaches should consider ways to recover both physically and emotionally.